Estratégias multimalhas para controle de corrente de inversores conectados à rede por meio do filtro LCL - Martins, Leandro Tomé (2018)
This master thesis presents contributions to the study and development of current control of the grid-tied inverter through an LCL filter, by using multiloop control strategies. In the first proposed scheme, the inner loop controlled variable is the inverter-side current. Thus the third-order original system is simplified to a second-order equivalent system, that behaves like a current source inverter connected to the grid through a CL filter. Based on this reduced-order system, a PR controller and a active damping (to attenuate the CL resonance) are designed in an outer loop. For these purposes, frequency response analysis and pole/zero maps are used as designing methods. In a second multiloop strategy, the filter capacitor voltage is used as controlled variable in an inner loop, and the simplified system is represented by a controlled-voltage source connected to the grid through an L filter. In an outer loop, a state-feedback controller is designed, where the feedback gains are associated to the internal system states and resonant controller states, which are included in the system model for tracking and harmonics rejection purposes. In both former multiloop strategies, a sliding mode controller is designed in the inner loop, due to its fast response dynamics and disturbance rejection capability, thus guaranteeing that the both loops can be designed independently. Simulation and experimental results are presented for both control strategies. Results in terms of tracking, grid background harmonics rejection and robustness against grid inductance variation show that the proposed control schemes comply with IEEE 1547 standard. Through a comparative analysis, some features of control strategies can be shown. The advantages of the first proposed scheme are mainly in regard to the inner loop, which is less dependent on the grid-side system parameters, whereas the second strategy depends directly on the grid-side inductance and voltage. On the other hand, the second control strategy is more advantageous in regard to the order-reduction of the equivalent system, which shows a first-order circuit behavior instead of the second-order behavior of the first proposed control scheme.